Assessing the Role of Public-School Council in Utilization of the Non-Salary Budget - M. Asif Nadeem, Zaib Un Nisa, Manzoor Husain Shah (JCTE, 2023)
The current quantitative study was designed to ascertain the utilization of the Non-Salary Budget (NSB) by engaging members of the School Council (SC) in the government schools of Punjab (Pakistan). The study's major aim was to identify the gap in the utilization of the problems such as transparency, and participation of members of school councils' problems regarding no salary budget (NSB) the public schools. This study's nature is descriptive. The population of this study comprised all rural and urban boys' and girls' public secondary schools situated in the District of Bahawalpur. A sample of 400 participants in 20 schools was chosen through a multistage sampling procedure. A self-prepared questionnaire was distributed among the randomly selected sample of 356 school heads, teachers, clerks, and school council members. Data were analyzed through statistical methods for frequency, percentage, mean of the data, Standard Deviation, and t-test. The results indicated that the school committee's role is to enhance educational facilities by using NSB. It faces a lack of parents' support regarding children's academic progress. It is recommended that regular pieces of training for school heads and school council committee members may be conducted after short periods. Orientation training about the role, responsibilities, and authorities of members of the school council must be conducted at the stage of composing a new school council committee at the Tehsil level.